Capitalism, the politics of hate, and everyday cosmopolitanisms. (September 2019) - Gledhill, John
This article takes its cue from Joel Kahn's reformulation of the Kantian account of cosmopolitanism, which highlights the way that 'popular' cosmopolitan practices tend to emerge between localized individuals and groups who are forced to live side by side with 'others', in the absence of impositions from above or outside that fracture the relations normally established between actors who 'cannot avoid offending each other' but recognize that they 'cannot do without associating peacefully'. We live in times in which an ever-expanding variety of postures of resentment and hate are being politically instrumentalized in different regions of the world, and not simply around ethno-racial, cultural, and religious difference. Although some of this may repeat past historical experiences or needs to be understood in terms of specific national or regional histories, the article explores how the contemporary politics of resentment and hate has new dimensions that can be linked to the mounting contradictions of neoliberal capitalism and the transformations that it has produced in politics, culture, sociality, personhood, and identity. Looking at the situations currently encountered in the North Atlantic world and Brazil, the analysis highlights the obstacles to reversing disturbing tendencies through the normal politics of contemporary representative democracy, but also shows how anthropological research reveals counter-movements to them in what are not always obvious places. This confirms the wisdom of Kahn's argument that we are often looking for solutions in the wrong places and with a misplaced confidence in the global beneficence of Western liberal traditions.